Artificial potential field algorithm for path control of unmanned ground vehicles formation in highway. Issue 20 (1st October 2018) - Wang, Shufeng; Zhang, Junxin; Zhang, Junyou
Abstract : The artificial potential field algorithm for path control of unmanned ground vehicles formation in highway is proposed. First, the basic unit is derived from decomposition‐iteration principle to improve formation stability and flexibility. Then, the virtual‐leader potential field (VLPF) and vehicle‐vehicle potential field are combined to generate the formation path in straight highway. Especially the VLPF function boundary is set as ellipse to adapt the highway environment. Finally, the formation in curved highway can be achieved through changing the ellipse's orientation and dimension. Simulation results demonstrate the effectiveness of the proposed algorithm.